2022
DOI: 10.1007/s40122-022-00406-9
|View full text |Cite
|
Sign up to set email alerts
|

CT-Guided Thermocoagulation of the Pterygopalatine Ganglion for Refractory Trigeminal Autonomic Cephalalgia

Abstract: Introduction: Trigeminal autonomic cephalalgia (TAC) is a type of one-sided cerebral painful headache, with attacks regularly accompanied by autonomic responses, such as tearing, runny nose, panic, nausea and vomiting on the affected side. Currently, the most common treatment strategies are drugs, nerve grafts and surgery. Clinical understanding of TACs is limited. Here, we report the case of thermocoagulation treatment of the pterygopalatine ganglion in an uncommon TAC under local anesthesia. Case Presentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…[16] Moreover, it has been implicated in the pathophysiology of cluster headaches. [17,18] Ma et al [10] reported the efficacy of CT-guided radiofrequency treatment of the sphenopalatine ganglion for trigeminal autonomic cephalalgia. Given the role of the pterygopalatine ganglion in the treatment of trigeminal autonomous headache, we decided to use it as a therapeutic target for post-HZO neuralgia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Moreover, it has been implicated in the pathophysiology of cluster headaches. [17,18] Ma et al [10] reported the efficacy of CT-guided radiofrequency treatment of the sphenopalatine ganglion for trigeminal autonomic cephalalgia. Given the role of the pterygopalatine ganglion in the treatment of trigeminal autonomous headache, we decided to use it as a therapeutic target for post-HZO neuralgia.…”
Section: Discussionmentioning
confidence: 99%
“…CT was used to design and determine the puncture routes. Two milliliters of 1% lidocaine were used for skin localization; further, a 10-cm radiofrequency needle with a 5-mm active tip was inserted into the pterygopalatine fossa under CT guidance [10] (Fig. 2).…”
Section: Case Seriesmentioning
confidence: 99%